Cross-Sectional Study for Detection and Risk Factor Analysis of ESBL-Producing Avian Pathogenic Escherichia coli Associated with Backyard Chickens in Pakistan - Muhammad Adnan Saeed; Muhammad Saqlain; Usman Waheed; Syed Ehtisham-; Aman Ullah Khan; Aziz ur Rehman; Muhammad Sajid; Farhan Ahmad Atif; Heinrich Neubauer; Hosny El-Adawy (MDPI AG, 2023)
The increasing incidence of extended-spectrum β-lactamase (ESBL)-producing Escherichia (E.) coli in backyard chicken farming in Pakistan is of serious concern. This study aimed to assess the prevalence, antimicrobial resistance patterns and risk factors associated with ESBL avian pathogenic E. coli (APEC) isolated from backyard chickens in the Jhang district, Punjab, Pakistan. In total, 320 cloacal swabs were collected from four breeds of backyard chicken (Aseel, Golden, Misri and Necked Neck). ESBL E. coli were phenotypically identified using double disc synergy test (DDST) and corresponding genes were confirmed by multiplex polymerase chain reaction (mPCR). Out of the 320 samples, 164 (51.3%) were confirmed as E. coli, while 74 (45.1%) were characterized as ESBL E. coli. The frequency of isolation of ESBL E. coli was highest in Aseel chickens (35.1%). Of the 164 confirmed E. coli, 95.1%, 78.6%, 76.8%, 71.3%, 70.1%, 68.9%, 60.4% and 57.3% were resistant against tylosin, doxycycline, cefotaxime, enrofloxacin, colistin, trimethoprim/sulfamethoxazole, chloramphenicol and gentamicin, respectively. The ESBL gene types detected and their corresponding proportions were blaCTX-M (54.1 %, 40/74), blaTEM, (12.2%, 9/74) and co-existence (blaCTX-M and blaTEM) were shown in 33.8% (25/74). The blaCTX-M gene sequence showed homology to blaCTX-M-15 from clinical isolates. The mean multiple antibiotic resistance index (MARI) was found to be higher among ESBL E. coli (0.25) when compared to non-ESBL E. coli (0.17). Both free-range husbandry management system (p = 0.02, OR: 30.00, 95% CI = 1.47-611.79) and high antimicrobial usage in the last 6 months (p = 0.01, OR: 25.17, 95% CI = 1.81-348.71) were found significantly associated with isolation of ESBL-producing E. coli in the tested samples using binary logistic regression analysis. This study confirmed the potential of backyard chickens as a reservoir for ESBL E. coli in the Jhang district, Punjab, Pakistan.